Laws and lawmakers science, metaphysics, and the laws of nature - Lange, Marc, 1963- (New York ; Oxford : Oxford University Press, 2009)
What distinguishes laws of nature from ordinary facts? What are the 'lawmakers': the facts in virtue of which the laws are laws? How can laws be necessary, yet contingent? Lange provocatively argues that laws are distinguished by their necessity, while also providing a non-technical and accessible survey of the field.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Philosophy of nature; Physical laws; Philosophy and science